Future directions: what LIES ahead for smart biochemical wearables in health monitoring? - Kharb, S. (Frontiers in Analytical Science, 2025)
Next-generation non-invasive biochemical wearables hold promise in transforming healthcare by providing real-time, continuous monitoring of biochemical markers. Non-invasive methods include smart tattoos, microneedle patches, wearable biosensors, flexible bioelectronics, implantable sensors, smart textiles, and smart contact lenses. A comprehensive picture of an individual’s health can be detected via critical markers such as glucose, lactate, cortisol, and volatile organic compounds (VOCs) from sweat, saliva, tears, breath and interstitial fluid (ISF)-based, non-invasive and minimally invasive biosensors using these advanced technologies. Personalized insights for enhancing their functionality are possible by integrating them with AI and big data analytics for early disease detection and proactive health management. This study explores the potential of futuristic biochemical wearables, their current status, underlying technologies, potential associated applications and challenges, and their positioning as transformative solutions in personalized healthcare for redefining the future of healthcare monitoring.